Perkembangan Teknologi Informasi dan Komunikasi terhadap Perubahan Sistem Komunikasi Indonesia - Detya Wiryany; Selina Natasha; Rio Kurniawan (Jurnal Nomosleca, 2022)
The role of information and communication technology is no less important than human food and clothing needs. A technology is essentially created to make human life easier and more comfortable. Through communication, humans build themselves and their environment, and through communication, human civilization becomes dynamic. This research method is descriptive qualitative with purposive sampling technique in determining five informants. Data collection techniques by observation, documentation and interviews and using data analysis Miles and Huberman. The existence of technology at that time helped the government's communication process, facilitated access to information, shortened time and cut costs. The development of information and communication technology is progressing very rapidly at this time so that it triggers changes in Indonesia's communication system. In conveying information or messages to other communities in urban and rural areas, of course, it was still very limited in the past, technology with all-improvement was very difficult to obtain information or communicate. Along with developments, today's communication system changes everything to be very easy and sophisticated.Keywords: Development of Technology, Information, Communication Systems